Am himmel wandre ich - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1992)
AM HIMMEL WANDRE ICH / IN THE SKY I AM WALKINGAmerican Indian songs for two voices (Helga Hamm-Albrecht, Karl O. Barkey)